2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5946377
|View full text |Cite
|
Sign up to set email alerts
|

Integrating binaural cues and blind source separation method for separating reverberant speech mixtures

Abstract: This paper presents a new method for reverberant speech separation, based on the combination of binaural cues and blind source separation (BSS) for the automatic classification of the time-frequency (T-F) units of the speech mixture spectrogram. The main idea is to model interaural phase difference, interaural level difference and frequency bin-wise mixing vectors by Gaussian mixture models for each source and then evaluate that model at each T-F point and assign the units with high probability to that source.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 11 publications
2
50
0
Order By: Relevance
“…We selected 15 utterances spoken by both male and female speakers at random of the same length (about 3s) and then shortened to 2.5 s as in [5].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We selected 15 utterances spoken by both male and female speakers at random of the same length (about 3s) and then shortened to 2.5 s as in [5].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work [1,3,5,7] suggested that by normalizing and pre-whitening the observation the results will be improved. Therefore we will normalize the amplitude of the observations as follows:…”
Section: The Observation Setmentioning
confidence: 99%
See 3 more Smart Citations